Optimized preparation and regeneration of MFI type base catalysts for d-glucose isomerization in water. Issue 10 (27th April 2020) - Antunes, Margarida M.; Fernandes, Auguste; Falcão, Diogo; Pillinger, Martyn; Ribeiro, Filipa; Valente, Anabela A.
Abstract : Eco-friendly solid bases possessing hierarchical MFI structure for d -glucose isomerization to d -fructose. Optimizing catalyst synthesis and composition for enhanced stability. Abstract : The isomerization of d -glucose to d -fructose is an important transformation in food and biomass chemistry, for which the use of robust heterogeneous catalysts instead of restrictive enzyme-based systems is desirable, although continues to be very challenging. Herein, solid base catalysts possessing a relatively robust hierarchical MFI structure and (non-toxic) alkali (M = Na, K) and alkaline-earth (Me = Ca, Mg) metals were prepared via top-down strategies and characterized via complementary techniques. The catalyst preparation and regeneration conditions were optimized to achieve superior performances. The highest catalyst stability was reached for the Mg, K-containing hierarchical zeotype prepared via solid-state impregnation (SSI) of Mg, which led to 65% d -fructose selectivity at 45% conversion, 100 °C, 2 h, or 99% selectivity at 26% conversion, 75 °C. The SSI is an up-scalable process which advantageously avoids the use of solvents, pre-preparation of alkaline liquid solutions and solvent evaporation stages for manufacturing eco-friendly catalysts.